Kearifan Lokal Sebagai Implementasi P5 Pada Kurikulum Merdeka Di SMA Pembangunan Laboratorium UNP - Aisyah Rahmadani; Hafizah Zarga Anggrayni; Nabila Muthia Rezky Maghfirah; Nashiro Jamila (Universitas Maritim AMNI Semarang, 2024)
This research discusses the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) in the Independent Curriculum at the UNP Laboratory Development High School. The Merdeka Curriculum emphasizes the character of students with six main dimensions, such as faith, diversity, mutual cooperation, independence, critical thinking and creativity. Implementation of P5 is carried out through project-based activities involving these elements, with a focus on the theme